Show me how u got it. Evaluate the function at the given value of the independent variable. Simplify the results.

f(x) = 1/sqrt(x-1)

Find:

[f(x) - f(2)] / (x-2)Evaluate the function at the given value of the independent variable?

[f(x) - f(2)]/(x-2)=[1-(sqrt(x-1)] / [sqrt(x-1) (x-2)]Evaluate the function at the given value of the independent variable?

f(2) = 1/sqrt(2-1) = 1/sqrt(1) = 1

f(x) - f(2) = [1/sqrt(x-1)] -1 =[1-sqrt(x-1)]/sqrt(x-1)

so the answer is [1-sqrt(x-1)] / [(x-2)sqrt(x-1)]

Subscribe to:
Post Comments (Atom)

## No comments:

## Post a Comment